(untitled) (International Journal of Food and Nutritional Sciences, 2022)
An excellent source of knowledge about the range of phytochemicals found in medicinal plants that can be precisely selected for use in drug development. The objective of the current study was to assess the qualitative phytochemical screening of Achyranthus aspera methanolic extract, which was followed by analysis using thin-layer chromatography (TLC) and high-performance thin-layer chromatography (HPTLC). Pre-coated silica gel G 60 F254 plates were subjected to TLC/HPTLC using a mobile phase that contained Toluene: Ethyl acetate (7:3v/v). The plates were grown at room temperature in the saturated mode of the twin trough chamber. In ultraviolet light, the bands were seen and captured on camera at 254 nm and 366 nm. Major peaks at 366 nm were found when Achyranthus aspera was scanned with a densitometer using a sample volume of 10 μl and a methanol concentration of 10 mg/ml. Numerous phytoconstituents, including alkaloids, flavonoids, terpenoids, saponins, polysaccharides, and glycosides, are confirmed to be present by the screening process. The present study may provide a scientific foundation for the plant, which has been traditionally utilized to treat a variety of illnesses including untested metabolic problems.